2017
DOI: 10.1038/emm.2017.22
|View full text |Cite
|
Sign up to set email alerts
|

Next-generation sequencing enables the discovery of more diverse positive clones from a phage-displayed antibody library

Abstract: Phage display technology provides a powerful tool to screen a library for a binding molecule via an enrichment process. It has been adopted as a critical technology in the development of therapeutic antibodies. However, a major drawback of phage display technology is that because the degree of the enrichment cannot be controlled during the bio-panning process, it frequently results in a limited number of clones. In this study, we applied next-generation sequencing (NGS) to screen clones from a library and dete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
56
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 63 publications
(58 citation statements)
references
References 22 publications
2
56
0
Order By: Relevance
“…Also, it was reported that clones with high binding activity to a target antigen can exist in a rare population in a library, due to the bias that results from the biopanning 8 . This was shown in our previous research, where certain rare clones in a library were retrieved and confirmed to have a binding activity to a target antigen 9 . Thus, to retrieve these rare clones with high developability and exploit them, in-depth analysis of a library is essential.…”
Section: Introductionsupporting
confidence: 69%
See 1 more Smart Citation
“…Also, it was reported that clones with high binding activity to a target antigen can exist in a rare population in a library, due to the bias that results from the biopanning 8 . This was shown in our previous research, where certain rare clones in a library were retrieved and confirmed to have a binding activity to a target antigen 9 . Thus, to retrieve these rare clones with high developability and exploit them, in-depth analysis of a library is essential.…”
Section: Introductionsupporting
confidence: 69%
“…Conventionally, in vitro screening has been used to identify and retrieve clones in a phage display library 10 . Next-generation sequencing (NGS) technology was introduced to improve the screening process in terms of sampling depth 9,11,12 . However, the two existing methodologies, the in vitro screening and the NGS-based process, still have several technical limitations in identifying and retrieving rare clones in the library in high throughput.…”
Section: Introductionmentioning
confidence: 99%
“…Besides directly mining natural B‐cell‐derived antibody repertoires of animals and humans, Ig‐seq can also be used to interrogate a diverse set of recombinant antibody libraries like naive, focused, immune, semi‐synthetic and fully synthetic libraries . These repertoires are compatible with in vitro screening platforms such as phage, yeast or ribosome display .…”
Section: Sequencing Recombinant Antibody Repertoiresmentioning
confidence: 99%
“…In order to more fully exploit the potential of various antibody libraries, several studies reported the combined use of traditional recombinant library screening and Ig‐seq analysis . In one of the first examples by Ravn et al ,.…”
Section: Combining High‐throughput Screening and Sequencing For Monocmentioning
confidence: 99%
See 1 more Smart Citation